Choledochal cysts--report of three cases and review. Issue 704 (June 1984) - Waldron, R.; Drumm, J.; McCarthy, C. F.; Murphy, B.
Abstract : Three cases of choledochal cyst are presented, with a review of previous publications. We re-emphasize the diagnostic dilemma involved and discuss current surgical management. A new complication is illustrated and an association with polycystic kidneys is reported. Choledochal cysts are uncommon, but correct management ensures a symptom-free future for the patient. Recent reports support cyst excision if technically feasible.